PREGNANCY WITH FIBROIDS AND ITS OBSTETRIC COMPLICATIONS - Noor, Shehla; Fawwad, Ali; Sultana, Ruqqia; Bashir, Rubina; ain, Qurat -ul-; Jalil, Huma; Suleman, Nazia; Khan, Alia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Pregnancy along with a fibroid is a high risk pregnancy which may lead to complication with unequal gravity. Objective of this study was to assess the prevalence and obstetric complications of fibroids during pregnancy, this cross-sectional study was carried out in the Department of Gynaecology, Unit ’˜C’, Ayub Teaching Hospital Abbottabad. Method: Data of all patients who presented with fibroid during pregnancy during two years, i.e., from Jan 2006 to Dec 2007 was recorded on a proforma and analysed using SPPS-12. Results: Thirty patients were diagnosed to have fibroids during pregnancy out of 3468 deliveries, thus prevalence was 0.865% in our hospital. The age of 50% cases was from 20 to 30 years, and 30 to 35 Year (27%). Twenty-one (70%) belonged to low socioeconomic status. Ninety percent patients reached up to term pregnancy between 37 to 40 weeks. Fibroids were found less common in patients in their first pregnancy (8, 23.66%). Twenty-one (70%) patients were delivered by caesarean section, and in 1 (3.33%) patient hysterotomy was performed. Failure to progress and foetal distress was the commonest indication for caesarean section (8, 38.09%) followed by breech presentation (4, 19.04%), cord prolapse (3, 14.28%) and fibroids in the lower segment (2, 9.52%). Anaemia was the commonest complication (20, 66.66%) followed by postpartum haemorrhage (PPH) (10, 33.33%). Breech presentation was the commonest malpresentation (4, 13.33%) associated with fibroids during pregnancy. Premature rupture of membranes and cord prolapse was seen in 3 (10%) patients each. Four (13.33%) patients underwent abdominal hysterectomy. Intra uterine growth restriction IUGR was seen in 2 patients (6.66%), 2 patients ended up with abortions, 1 patient had a spontaneous pregnancy loss and the other underwent hysterotomy due to low lying placenta and heavy bleeding per vaginum. Compound presentation, neglected transverse lie, stuck head of breech, placenta increta, retained placenta, low lying placenta, were the other complications occurring in one patient each. One patient died during anaesthesia. Neonatal outcome was encouraging as 20 (67%) babies were of average birth weight and only 4 (13.33%) babies had low APGAR score and needed NICU admission. Perinatal mortality was 37/1000 live births. Conclusion: Pregnancy with fibroids leads to increase in caesarean section rate due to dysfunctional labour and malpresentation. There is also increased incidence of post partum haemorrhage along with associated complication of anaemia, anaesthesia and surgery. Keywords: Fibroid, leiomyoma, pregnancy